2019
DOI: 10.1101/854216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative Genomic Analysis and Functional Studies Reveal GP5, GRN, MPO and MCAM as Causal Protein Biomarkers for Platelet Traits

Abstract: Rationale Mean platelet volume (MPV) and platelet count (PLT) are platelet measures that have been linked to cardiovascular disease (CVD) and mortality risk. Identifying protein biomarkers for these measures may yield insights into CVD mechanisms.Objective We aimed to identify causal protein biomarkers for MPV and PLT among 71 CVDrelated plasma proteins measured in Framingham Heart Study (FHS) participants. Methods and ResultsWe conducted integrative analyses of genetic variants associated with PLT and MPV wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This suggests that the consequence of neutrophil emperipolesis by MKs is not only a BM phenomenon, but has ramifications for circulating platelets. Indeed, the transfer of membrane between MKs and neutrophils during emperipolesis has been recently reported 41 and a recent functional genomic study has suggested the association of Mpo, known to localize to neutrophil specific granules, with mean platelet volume highlighting the cross-talk between neutrophils and platelets 42 . Our proteomic dataset strongly supports the reduction of neutrophil specific granules in GPS, an observation that has previously been con-tested 12,13,18 , and shows for the first time that gelatinase granule constituents are also depleted from GPS neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the consequence of neutrophil emperipolesis by MKs is not only a BM phenomenon, but has ramifications for circulating platelets. Indeed, the transfer of membrane between MKs and neutrophils during emperipolesis has been recently reported 41 and a recent functional genomic study has suggested the association of Mpo, known to localize to neutrophil specific granules, with mean platelet volume highlighting the cross-talk between neutrophils and platelets 42 . Our proteomic dataset strongly supports the reduction of neutrophil specific granules in GPS, an observation that has previously been con-tested 12,13,18 , and shows for the first time that gelatinase granule constituents are also depleted from GPS neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of membrane between MKs and neutrophils during emperipolesis has been reported, 55 and a recent functional genomic study reported an association of Mpo, known to localize to neutrophil-specific granules, with mean platelet volume highlighting the cross-talk between neutrophils and platelets. 56 Hence, the release of neutrophil granule proteins inside MKs during emperipolesis would provide a plausible explanation for the higher level of these proteins in GPS platelets.…”
Section: Discussionmentioning
confidence: 99%